Dynamics in Legislative Budgeting in Italy: 1982-2001 - Forestiere, Carolyn (Institutional Knowledge at Singapore Management University, 2006)
For much of the First Republic, the Italian Parliament was notorious for its fiscal irresponsibility. However, using data over a 20-year period we note that the performance of the Parliament during the passage of the national budget changed over time. During most the 1980s the Parliament always spent more than the amount specified in the government’s Budget Bill. But this trend slowed towards the late 1980s, and of particular interest is that for several years during the 1990s the Parliament voted to spend less than what the government originally proposed. We explain this anomaly using institutional theories and contextual explanations.